Interfacial Charge Transfer and Ultrafast Photonics Application of 2D Graphene/InSe Heterostructure - Jialin Li; Lizhen Wang; Yuzhong Chen; Yujie Li; Haiming Zhu; Linjun Li; Limin Tong (Nanomaterials, 2022)
Interface interactions in 2D vertically stacked heterostructures play an important role in optoelectronic applications, and photodetectors based on graphene/InSe heterostructures show promising performance nowadays. However, nonlinear optical property studies based on the graphene/InSe heterostructure are insufficient. Here, we fabricated a graphene/InSe heterostructure by mechanical exfoliation and investigated the optically induced charge transfer between graphene/InSe heterostructures by taking photoluminescence and pump–probe measurements. The large built-in electric field at the interface was confirmed by Kelvin probe force microscopy. Furthermore, due to the efficient interfacial carrier transfer driven by the built-in electric potential (~286 meV) and broadband nonlinear absorption, the application of the graphene/InSe heterostructure in a mode-locked laser was realized. Our work not only provides a deeper understanding of the dipole orientation-related interface interactions on the photoexcited charge transfer of graphene/InSe heterostructures, but also enriches the saturable absorber family for ultrafast photonics application.